2007
DOI: 10.1063/1.2426379
|View full text |Cite
|
Sign up to set email alerts
|

The low field microwave effective linewidth in polycrystalline ferrites

Abstract: High precision measurements on the low and high field effective linewidth ΔHeff at 10GHz have been made on ultradense (UD) and conventionally sintered (CS) polycrystalline yttrium iron garnet (YIG) materials. The high field data confirm previous results on the role of two magnon scattering to low wave number (k) electromagnetic Larmor branch spin waves that lie below the light line. The low field data reveal two important contributions to the effective linewidth. For a field regime from the low k edge of the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 11 publications
2
13
0
Order By: Relevance
“…The linewidth gets broadened with increasing resonance frequency. A similar trend in linewidth with frequency has been previously observed in ferrites [24]. We are unable to observe a linear correlation of resonance and external field over the frequency range 27-40 GHz, which can be described by Kittel's formulae [25].…”
Section: Resultssupporting
confidence: 72%
“…The linewidth gets broadened with increasing resonance frequency. A similar trend in linewidth with frequency has been previously observed in ferrites [24]. We are unable to observe a linear correlation of resonance and external field over the frequency range 27-40 GHz, which can be described by Kittel's formulae [25].…”
Section: Resultssupporting
confidence: 72%
“…Figure 17 shows the effective linewidth measured for polycrystalline YIG. 53 These linewidths have been studied also for ferrite thin films. It has been demonstrated that high quality epitaxial films with microwave losses equal to those in bulk crystals can be produced.…”
Section: Equation 103mentioning
confidence: 99%
“…The physical origin of losses in polycrystalline ferrites, through its effects on the line width, has been recently investigated in detail; the dominant role of grain boundaries is apparent [42,43]. As SmeGd content increases the intensity of the signal decreased (Fig.…”
Section: Electron Paramagnetic Resonancementioning
confidence: 99%